2012
DOI: 10.1007/s13042-011-0067-3
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid heuristics for the single machine scheduling problem with quadratic earliness and tardiness costs

Abstract: In this paper we present three hybrid heuristics for the single machine scheduling problem with quadratic earliness and tardiness costs, and no machine idle time. Our heuristic is a combination of a steady-state genetic algorithm and three improvement procedures. The two computationally less expensive of these three improvement procedures are used inside the genetic algorithm to improve the schedule obtained after the application of genetic operators, whereas the more expensive one is used to improve the best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Many approaches have been proposed for solving scheduling problems. Genetic algorithms (GAs) have been widely adopted in recent years and have proved to be suitable for various scheduling problems (Hallah 2007;Jolai et al 2007;Singh et al 2012;Hamidinia et al 2012).…”
Section: Equivalence Of Uncertain Modelsmentioning
confidence: 99%
“…Many approaches have been proposed for solving scheduling problems. Genetic algorithms (GAs) have been widely adopted in recent years and have proved to be suitable for various scheduling problems (Hallah 2007;Jolai et al 2007;Singh et al 2012;Hamidinia et al 2012).…”
Section: Equivalence Of Uncertain Modelsmentioning
confidence: 99%
“…Jolai et al [17] developed a GA for a single machine problem of minimizing the number of tardy jobs and maximum earliness. Singh et al [31] proposed three hybrid heuristics for a single machine scheduling problem with quadratic earliness and tardiness costs. Three improvement procedures were used and computational results showed that the hybrid approaches are very effective.…”
Section: Theoremmentioning
confidence: 99%
“…Also, the linear earliness and squared tardiness problem was considered by Schaller [16], Valente [17][18][19], Valente and Schaller [20], and Behnamian and Zandieh [21]. The problem with both quadratic earliness and quadratic tardiness costs was studied by Valente and Alves [22], Valente and Moreira [23], Valente [24], Valente et al [25], Singh et al [26], Kianfar and Moslehi [27], and Vilà and Pereira [28]. A large number of papers have been published on the total weighted tardiness problem.…”
Section: Introductionmentioning
confidence: 99%